Photoinduced Transformation of Uranyl Nitrate Crown Ether Compounds. Issue 2 (10th December 2020) - Blanes Díaz, Anamar; Kravchuk, Dmytro V.; Peroutka, Allison A.; Cole, Erica; Basile, Madeline C.; Forbes, Tori Z.
Abstract: The uranyl cation, (U(VI)O2 ) 2+, has previously demonstrated photocatalytic reactivity in organic solutions, which results in the formation of uranyl peroxide species. Past studies indicated that the phototransformation process typically ends with the formation of uranyl peroxide solid phases. In the current study, we explore the transformation of uranyl nitrate crown ether complexes, (18‐crown‐6)[UO2 (NO3 )2 (H2 O)2 ] ⋅ 2 H2 O (1 a ), (18‐crown‐6)[UO2 (NO3 )2 (H2 O)2 ] (1 b ), and (18‐crown‐6) [K(18‐crown‐6)] [(UO2 )2 (OH)2 (NO3 )4 (H2 O)4 ] (2 ) in the presence of ethanol to create a uranyl peroxide intermediate phase, (18‐crown‐6)[(UO2 )2 (O2 )(NO3 )2 (H2 O)4 ] (3 ), followed by a second alteration to a black solid (4 ). These compounds were structurally evaluated using both single‐crystal and powder X‐ray diffraction and then further characterized using Raman, NMR, and XPS spectroscopy. The initial transformation from the yellow uranyl nitrate phase (1 a, 1 b, and 2 ) to the uranyl peroxide (3 ) follow previously reported mechanisms. The second transformation to the black phase (4 ) is likely due to additional degradation of the 18‐crown‐6 molecule as a result of hydrogen abstraction and ring‐opening. In addition, we discuss the nature of confinement effects to impact the hydrogen abstraction process and the possibility that nitrate anions in the system may synergistically enhance the degradation process and lead to the formation of 4 . Abstract : A range of uranyl nitrate crown‐ether compounds was observed to undergo a photoinduced transformation into uranyl peroxide compound intermediates with subsequent solid‐state degradation into a black amorphous solid. The mechanism of such transformation was probed using X‐ray diffraction, Raman, NMR, and XPS spectroscopy, which demonstrated the degradation of crown‐ether molecules from within the material.